A Cross-sectional study among Hospital Employees- Metabolic Syndrome and Shift Work - Santhosh E Kumar; Antonisamy B; Henry Kirupakaran; Reginald G Alex (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Shift workers and metabolic syndrome are on the rise in developing nations. The link between Metabolic syndrome and shiftwork is not clear. This study aims to measure the prevalence of metabolic syndrome among shift workers and daytime workers and to assess the association between metabolic syndrome and shift work. Methods: Cross- sectional study was done in a South Indian hospital. Participants were selected via systematic random sampling between the age group of 25 -50 years. There were two study groups – day and shift workers. Sample size calculation was done with an alpha error of 0.05 and power of 80% to detect a 12.5% difference for metabolic syndrome prevalence between the two groups. Outcomes studied include the prevalence of metabolic syndrome and odds of developing metabolic syndrome among shift workers. The Chi-square test and independent t-test were the tests of significance used. The impact of relevant parameters on metabolic syndrome was assessed using univariate and multivariable analysis. Results: Eighty employees were studied in each group. At baseline, differences include; daytime workers were older in age, had a better quality of sleep, were less active physically, and consisted of more vegetarians. The prevalence of metabolic syndrome prevalence was thirty-three percent among the participants. The odds ratio (adjusted for relevant confounders) for shift workers to develop metabolic syndrome was 0.55 (95% CI 0.24 -1.29). Conclusion: Metabolic syndrome was diagnosed in a third of the hospital employees studied. There was no statistical difference between shift and daytime workers for the prevalence of metabolic syndrome. Increased awareness, screening, and preventive measures of the disease are recommended.Keywords: daytime, hospital, metabolic syndrome, shift work, sleep